Playing to win how strategy really works - Lafley, A. G. (Alan G.); Martin, Roger L.,author (Boston, Massachusetts Harvard Business Review Press, 2013)
Strategy is not complex. But it is hard. It's hard because it forces people and organizations to make specific choices about their future -- something that doesn't happen in most companies. In this book, two well-known business thinkers get to the heart of strategy -- explaining what it's for, how to think about it, why you need it, and how to get it done.
Introduction : how strategy really works -- Strategy is choice -- What is winning -- Where to play -- How to win -- Play to your strengths -- Manage what matters -- Think through strategy -- Shorten your odds -- Conclusion : the endless pursuit of winning.
Includes bibliographical references (p. [239]-243) and index.
Keywords: Procter & Gamble Company; Strategic planning; Success in business; Organizational change